Amputations of Lower Limb in Subjects with Diabetes Mellitus: Reasons and 30-Day Mortality. (26th July 2021) - Walicka, Magdalena; Raczyńska, Marta; Marcinkowska, Karolina; Lisicka, Iga; Czaicki, Arthur; Wierzba, Waldemar; Franek, Edward
Abstract : Background . Diabetic foot is one of the leading causes of patient disability worldwide. Lower-extremity amputations (LEAs) resulting from this disease massively decrease quality of life, the function of the patient, and incur significant healthcare costs. The aim of this study was to assess trends in the number of amputations, the diagnosis at discharge, and diagnosis-related mortality after LEA procedures in a nationwide population. Methods . Datasets of the National Heath Fund containing information about all services within the public healthcare system in Poland, spanning the years 2010-2019, were analyzed. The source of data regarding mortality was the database of the Polish Ministry of Digital Affairs. Results . Between 2010 and 2019, the annual number of amputations in patients with diabetes increased significantly from 5, 049 to 7, 759 (p for trend < 0.000001 ). However, the number of amputations in patients with diabetes calculated as a number per 100, 000 diabetics decreased significantly (p for trend < 0.0005 ) during this period. Amputations in patients with diabetes accounted for a majority of all amputations; the mean percentage of amputations in patients with diabetes was 68.6% of all amputations (from 61.1% in 2010 to 71.4% in 2019, p for trend < 0.0000001 ). The most common disease diagnosed at discharge after LEA in diabetic patients was diabetes itself. Vascular pathologies, such as soft-tissue/bone/joint infections and ulcerations, were the next most common. The 30-day mortality rate after LEA was rather high in patients with, as well as without, diabetes (depending on the cause for amputation 3.5-34% and 2.2-28.99%, respectively). Conclusions . The number of LEA in patients with diabetes in Poland increased substantially between 2010 and 2019 along with an increasing number of diabetics. Vascular pathologies, infections, and ulcerations were the most common causes of LEA. The 30-day mortality rate after amputation was rather high and varied depending on the diagnoses at discharge.